2000
DOI: 10.1152/ajplung.2000.279.2.l360
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ras-dependent ERK activation in phorbol ester-induced endothelial cell barrier dysfunction

Abstract: The treatment of endothelial cell monolayers with phorbol 12-myristate 13-acetate (PMA), a direct protein kinase C (PKC) activator, leads to disruption of endothelial cell monolayer integrity and intercellular gap formation. Selective inhibition of PKC (with bisindolylmaleimide) and extracellular signal-regulated kinases (ERKs; with PD-98059, olomoucine, or ERK antisense oligonucleotides) significantly attenuated PMA-induced reductions in transmonolayer electrical resistance consistent with PKC- and ERK-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
92
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 59 publications
14
92
0
1
Order By: Relevance
“…In addition, PKC, independent of Ras, plays a critical role in angiotensininduced Raf1 and MEK activation in cardiac myocytes (Zou et al, 1996), and PKCd activates the MEK/ERK pathway, independent of Ras but dependent on Raf activation, in COS and NIH-3T3 cells (Ueda et al, 1996;Seternes et al, 1999). In contrast, other studies have shown that PMA/PKC regulates downstream gene induction and functions through sequential induction of Ras, Raf and MEK (Chiloeches et al, 1999;Verin et al, 2000;Vuong et al, 2000); these effects appear to be dependent on cellular context. In our present study, cotransfection with a dominant-negative Raf effectively inhibited TRAF1 promoter induction by PMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PKC, independent of Ras, plays a critical role in angiotensininduced Raf1 and MEK activation in cardiac myocytes (Zou et al, 1996), and PKCd activates the MEK/ERK pathway, independent of Ras but dependent on Raf activation, in COS and NIH-3T3 cells (Ueda et al, 1996;Seternes et al, 1999). In contrast, other studies have shown that PMA/PKC regulates downstream gene induction and functions through sequential induction of Ras, Raf and MEK (Chiloeches et al, 1999;Verin et al, 2000;Vuong et al, 2000); these effects appear to be dependent on cellular context. In our present study, cotransfection with a dominant-negative Raf effectively inhibited TRAF1 promoter induction by PMA.…”
Section: Discussionmentioning
confidence: 99%
“…Raf-1, but not Ras, mediates TRAF1 activation by PMA PMA/PKC can activate MEK/ERK through Rasdependent or -independent pathways (Ueda et al, 1996;Verin et al, 2000;Vuong et al, 2000;Zhao et al, 2001). We next determined the role of Ras and Raf in TRAF1 stimulation.…”
Section: Involvement Of Mek/erk In Traf1 Stimulation By Pmamentioning
confidence: 99%
“…Another well-known effect of PMA is the activation of Erk1/2 MAP kinase pathway (Frost et al, 1994;Verin et al, 2000). At least three of the five protein classes directly activated by PMA (i.e., PKC, Ras-GRP, chimaerin) could transduce their transcriptional signals via the MAP kinase pathway (Kazanietz, 2002).…”
Section: Pv1 Upregulation Requires the Activation Of Erk1/2 Map Kinasmentioning
confidence: 99%
“…MAPK inhibitor: PD98059 (2-(2-Hydroxyethylamino)-6-benzylamino-9-methylpurine; Calbiochem; Verin et al 2000, Xiao et al 2004) was injected as a single dose of 0·5, 5, 50 µg in 4 µL of 0·1% DMSO.…”
Section: Treatmentsmentioning
confidence: 99%